PELAKSANAAN ASESMEN TERHADAP OKNUM ANGGOTA KEPOLISIAN SEBAGAI PENGGUNA NARKOTIKA UNTUK MENDAPATKAN REHABILITASI POLRESTABES MAKASSAR - Jamal, Agustiawan; Renggong, Ruslan; Siku, Abdul Salam (Postgraduate Bosowa University Publishing, 2019)
This study aims to determine the implementation of assessments to obtain rehabilitation for drug users by members of the police, as well as knowing the factors that become obstacles in the implementation of assessments in handling narcotics users by members of the police. The research method used is descriptive analysis with data from field interviews and literature. The results showed that the person detected using narcotics will be carried out an assessment process to develop a case carried out by the Narcotics Unit unit investigator Polrestabes Makassar to find out where their involvement was as a dealer, precursor or just a user. While the process of enforcing the code of ethics does not directly take firm action against members who are caught in criminal cases of narcotics abuse. The inhibiting factors in the enforcement of narcotics criminal law by the police are the application of sanctions to members of the police who commit violations. As well as a sense of solidarity between fellow members of the National Police, problems with inadequate facilities and infrastructure and limited budget support.